A Política de Socioeducação no estado do Paraná e a transição do Sistema Estadual de Atendimento Socioeducativo (2007 – 2015) - Oliveira, Renata Hoeflich Damaso de (2018)
This study analyzes the impact of the management of the Socio-education Policy of the state of Paraná, from 2007 to 2015, considering the transition of the State System of Socio-Educational Assistance of the Secretariat of State for Children and Youth - SECJ to the Secretariat of State for Family and Social Development - SEDS and the Secretariat of State for Justice, Citizenship and Human Rights - SEJU. From the study of the structuring of the Socioeducation Policy in the state of Paraná, it presents the genesis of the service to adolescents in conflict with the law. Primary sources identified as laws, decrees, deliberations and resolutions were collected on official websites such as the State Council for the Rights of Children and Adolescents - CEDCA, the State System of Legislation of the State of Paraná, as well as on the websites of the secretariats SEDS and SEJU were analyzed and complemented by theses and dissertations, culminating in the study of the structuring of the Socioeducation Policy in the state of Paraná. The analysis of the management of the Socio-Education Policy of the State of Paraná, from 2007 to 2015, considering the reorganization of the service to adolescents in conflict with the law, demonstrated that there is a certain discontinuity in the programs developed to this population, since each change of institutional locus also alter the programs, having different actions to be implemented in the Socio-educational Assistance System. The programs have increasingly presented an emphasis on individual adolescent empowerment, refining the logic of individual accountability with the transfer of collective responsibility to the subject, disregarding the consequences of social relations of production.